The Effect Of Customer Value And Brand Awareness On Customer Retention With Customer Satisfaction As A Mediating Variable - Bella Octavia (Journal Research of Social Science, Economics, and Management, 2023)
This research was conducted to analyze more deeply the influence of customer value and brand awareness on customer retention with customer satisfaction as a mediating variable. The survey data used in this research is based on the results of a questionnaire distributed online using a Google form consisting of 18 questions and filled in by 291 respondents. The data was then processed using AMOS version 23. The results of this research prove that customer value and brand awareness have a positive and significant effect on customer retention with customer satisfaction as a mediating variable. It is hoped that the results of this research will bring positive benefits to various parties, namely for business owners and the world of fast commerce as well as for science in theory development. This research has sample and time limitations. So it can be a suggestion for further research to conduct research with a larger sample and at a different time. So it is recommended for future researchers to dig deeper into the scope of quick commerce, research over a wider area and use different research methods.